2024
DOI: 10.1149/2162-8777/ad325c
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Rare Earth Nd and Sm Doping on the Structural, Morphological, Optical, Magnetic, and Electromagnetic Traits of Mg-Zn-Cu Spinel Nanoferrites

Anand Sharma,
Rohit Jasrotia,
Nisha Kumari
et al.

Abstract: Magnetic nanoparticles of neodymium and samarium substituted Mg-Zn-Cu, with a chemical composition of Mg0.5Zn0.5Cu0.05RxFe1.95-xO4 (x = 0.05; R = Nd, Sm) were produced via the sol-gel auto-combustion route. X-ray diffraction indicates the evolution of a cubic symmetry having Fd3m space group and no impurities at room temperature. Field-emission scanning electron microscopy images show irregularly-shaped and agglomerated grains in all samples. Fourier transform infrared examination reveals stretching vibrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…[3][4][5][6] Due to these traits, it has potential applications in the various research sectors, including, the catalysis, energy, recording media, permanent magnets, switching devices, microwave, high frequency etc. 1,7,8 Hence, because of these prospective applications and traits, the spinel nanoferrites are considered as the important material.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Due to these traits, it has potential applications in the various research sectors, including, the catalysis, energy, recording media, permanent magnets, switching devices, microwave, high frequency etc. 1,7,8 Hence, because of these prospective applications and traits, the spinel nanoferrites are considered as the important material.…”
Section: Introductionmentioning
confidence: 99%
“…Moon et al 12 worked on the epoxy adhesive with rGO reinforcement and have shown that the mechanical properties of NC increased by using rGO. Wejrzanowski et al 13,14 have shown enhanced results of experimental work & numerical simulation where copper is reinforced with multi-layered Gr to enhance the thermal conductivity of NC. Peng et al have improved solder efficiency by adding Gr into Sn-Bi NC.…”
mentioning
confidence: 99%
“…1 The magnetic materials have shown their importance in different areas of technologies including, magnetic recording media, gas sensors, wastewater treatment, inductors, switching circuits, stealth technologies, biomedical etc. [2][3][4][5][6][7] Spinel ferrite has risen above the other types of ferrites in terms of applicability in many technologies. The most important application of spinel ferrite which might have a very huge impact on our society is the wastewater treatment through photocatalysis.…”
mentioning
confidence: 99%